A comparative study, distribution, predicted no-effect concentration (PNEC) and contamination assessment of phenol with heavy metal contents in two coastal areas on the Egyptian Mediterranean Sea coast. (July 2022) - El Zokm, Gehan M.; El-Said, Ghada F.; El Ashmawy, Ahmed A.
Abstract: This study comparing the expected pollution status of phenol along with heavy metals in sediments of two economic regions on the Mediterranean Sea coast using equilibrium partitioning method (EPM) as well as exposure of fishermen and populations to these sediments through ingestion and skin contact while swimming. El-Dekhila (ED) and Abu Talat (AT) regions were different in sediment texture and pollution sources. The expected ecological hazards of phenol in the studied areas were carried out using the equilibrium partitioning method (EPM) by which the partition coefficient of organic carbon-water, K OC ( logK OC > 0.95–3.49), octanol-water coefficient, K OW ( logK OW > 1.46–1.48) and sediment/liquid partition coefficient, K d (log K d < 3) detected high availability amounts of phenol in seawater. Risk quotient ( RQ ) for phenol in ED region ranged from high to moderate risk, while for AT region was low risk (<0.1); whereas, RQ values of heavy metals in sediments of two studied areas reflected the overall low risk without human hazards ( HQ & HI < 1). RQ Acute and RQ Chronic values were above 1 for phenol and heavy metals (Cu and Zn) reflecting that fish were the most sensitive to them in the two regions. Interestingly, this current investigation predicts future contamination of the studied areas especially phenol contamination and its relationship to heavy metals using some reasonable information and allowing the managers to manage how they decide on and protect these two areas. Thus, there is a constant need to use relatively simple tools capable of ensuring protection objectives with a quantity of information with realistic feasibility. Graphical abstract: Image 1 Highlights: A Comparative study to evaluate the expected future pollution to phenol and heavy metals in two Egyptian coastal areas on the Mediterranean Sea. The expected future pollution in the study areas was estimated using equilibrium partitioning method (EPM). The ecological risk assessment has been studied through many different sediment guidelines and integrated ecological indices. The path of ingestion and dermal exposure of children and adults while swimming to phenol and heavy metals were evaluated in the two studied areas.